Linear Multistep Methods and Order Stars: Some Properties - Ferreira, J.C.; Meira, S.A.; Meneguette Jr., M.; Nogueira, J.R. (Trends in Computational and Applied Mathematics, 2008)
Order stars theory, introduced by Wanner et al (1978), have become a fundamental tool for understanding of order and stability properties of numerical methods. In this work we intend to study some properties of numerical linear multistep methods using this theory.